Kilka uwag metodologicznych na marginesie książki Anny Janoty-Stramy - Rychel-Mantur, Dominika (Instytut Historii im. Tadeusza Manteuffla Polskiej Akademii Nauk, 2025)
This review article provides a critical analysis of Anna Janota-Stramy’s book on the image of Napoleon in nineteenth-century Polish memoirs. It criticises the methodology used, emphasising shortcomings that largely stem from uncertainty about adopting one definition of a memoir. The article also polemicises with some of the author’s statements. It reflects on the origins and achievements of Napoleonic historiography, highlighting areas that require further research, such as the administration and economy of the Duchy of Warsaw, as well as biographies of leading figures.
p. 355-385
Concerns book: Obraz Napoleona Bonaparte w polskim pamiętniku = L'image de Napoléon Bonaparte dans les mémoires polonaises / Anna Janota-Strama.- Warszawa : Wydawnictwo DiG ; Bellerive-sur-Allier : Edition La Rama, 2023.
Summary in English.
Keywords: Napoleon I (Emperor of the French; 1769-1821); Poles; Duchy of Warsaw; memoirs of the Napoleonic era; Polish memoir writing